The effect of internal control and anti-fraud awareness on fraud prevention (A survey on inter-governmental organizations) - Rozmita Dewi YR; Irfan Ariandi (Universitas Hayam Wuruk Perbanas, 2017)
The objectives of this research are to analyze the effect of internal control and anti-fraud awareness on the fraud prevention in inter-governmental organization. Fraud prevention is devoted in the procurement process. This study used internal control and anti-fraud awareness as independent variable, while fraud prevention as the dependent variable. In addition, it also used a convenience sampling for collecting the data. The sample of the data was taken using questionnaires which were distributed to Indonesian Staff who had been involved or they had participated in the procurement process. The total number of the sample was 58 respondents. Furthermore, the data were analyzed by means of multiple regressions. The results showed that internal control and anti-fraud awareness have significant effects on fraud prevention. It indicates that the action of doing fraud can be prevented by establishing a good internal control and increasing anti-fraud awareness to all parties in the organization.